Viscous dissipation and radiative effects in the magneto-micropolar fluid with partial slip and convective boundary condition - G. Thirupathi; K. Govardhan; G. Narender (Surveys in Mathematics and its Applications, 2022)
In this article, the numerical study of the flow of micro polar fluid above a porous stretching sheet in the presence of viscous dissipation, thermal radiation, flow on an unsteady stretching surface and magnetohydrodynamic with heat transfer through moving fluid is discuses. A proper similarity transformation is utilized to convert the boundary layer equations into the nonlinear and coupled ordinary differential equations. These ODEs are sorted out numerically by applying the shooting mechanism. Graphical representations are also included to explain the effect of evolving parameters against the above-mentioned distributions. Finally, the numerical outcomes are discussed at the end of the article.